Bundled agroecological cacao production practices: fertilizer and sustainable practices training benefits over 200 organic producers. - Mockshell, Jonathan; Ritter, Thea; Blanco, Maria; Ngige, Chris Mwangi; Mosquera, Leslie Estefany; Sánchez Choy, José G.; Ivanova, Yovita (2025)
Organic fertilizers boost yields, yet according to our research, most cacao producers in Ucayali region do not use fertilizers year-round, due to limited finances and knowledge. We trained 69 organic cacao producers, who are now adopting innovative bundled agroecological practices to significantly enhance their productivity. Bundles of practices include preparing and applying organic fertilizers to improve managing solid organic waste generated from cacao production. Expected scalable outcomes include enhanced soil health, recycling, cacao production, and incomes.